Ballistics - Rollins, Barbara B.; Dahl, Michael (Mankato, Minn. : Capstone Press, 2004)
Describes the science of ballistics, including the types of weapons and ammunition used in crimes, clues guns and bullets leave behind, techniques used by ballistics experts, and how ballistics evidence is used to solve crimes.
Weapons fired! -- Firearms and ammunition -- Comparing bullets and cartridge cases -- Other firearm evidence.
Includes index.
Keywords: Forensic ballistics -- Juvenile literature; Criminal investigation -- Juvenile literature; Evidence, Criminal -- Juvenile literature; Ballistics; Forensic sciences; Criminal investigation; Evidence, Criminal